Integrated Process of Coal Fast Pyrolysis in a Fluidized Bed Reactor With Reforming Reaction of Simulated Fuel Gas to Promote Light Tar Evolution - Li, Chao; Luo, Zhongyang; Fang, Mengxiang; Yan, Qike; Cen, Jianmeng (Frontiers in Energy Research, 2021)
The evolution behavior of the light tar during coal fast pyrolysis under inert gas, simulated fuel gas atmosphere (SFG) and catalytic reformation of simulated fuel gas (CRS) over Ni/Al2O3 was studied in this paper. The light tar was recovered from distillation of crude tar at the temperature of 300℃ and subsequently subjected to detection through GC-MS analysis. It was found both SFG and CRS over Ni/Al2O3 significantly enhanced light tar yield, but was shown little effect on the heavy tar yield. According to molecular structure characteristics, the compounds in light tar could be classified into several groups: aromatic components, phenol components, aliphatic components, heteroatom components and O-containing components (phenol compounds excluded). It was demonstrated that the selectivity of each components in light tar varied significantly with pyrolysis atmosphere and temperature. The evolution of aromatic components took the dominant role in light tar produced at high temperature. The SFG and CRS contributed markedly to enhance evolution of O-aromatic components in light tar, whereas suppressed evolution of O-aliphatic components and phenol components in light tar at high temperature.